A graph neural network model application in point cloud structure for prolonged sitting detection system based on smartphone sensor data - Hardjianto, Mardi; Istiyanto, Jazi Eko; Tjoa, A. Min; Syahrulfath, Arfa Shaha; Purnama, Satriawan Rasyid; Sari, Rifda Hakima; Hakim, Zaidan; Fuadin, M. Ridho; Ananto, Nias (ETRI journal, 2025)
The prolonged sitting inherent in modern work and study environments poses significant health risks, necessitating effective monitoring solutions. Traditional human activity recognition systems often fall short in these contexts owing to their reliance on structured data, which may fail to capture the complexity of human movements or accommodate the often incomplete or unstructured nature of healthcare data. To address this gap, our study introduces a novel application of graph neural networks (GNNs) for detecting prolonged sitting periods using point cloud data from smartphone sensors. Unlike conventional methods, our GNN model excels at processing the unordered, three‐dimensional structure of sensor data, enabling more accurate classification of sedentary activities. The effectiveness of our approach is demonstrated by its superior ability to identify sitting, standing, and walking activities—critical for assessing health risks associated with prolonged sitting. By providing real‐time activity recognition, our model offers a promising tool for healthcare professionals to mitigate the adverse effects of sedentary behavior.